Neutron Diffraction Study on the Magnetic Structure of Pr6Fe13Sn - Suharyana Suharyana; J.M. Cadogan; A. Rianaris (PPIKSN-BATAN, 2010)
We have successfully prepared a Pr6Fe13Sn sample by employing argon arc melting. The crystal structure of the sample has been examined by an x-ray diffraction. The x-ray pattern reveals that the sample crystallize in the tetragonal Nd6Fe13Si structure type with space group I4/mcm. Neutron diffraction at 150K performed on a powder sample shows a collinear antiferromagnetic ordering of the Fe and Pr sublattices with the wave vector (0, 0, 1) and an Ip type magnetic lattice with anti-centering translation. The main axis of antiferromagnetism is restricted to the (0 0 1) plane. The average refined Fe moments at 150 K is (2.0±0.4) µB whereas the Pr moments are (2.1±0.4) and (1.9±0.4) µB for the 8f and 16l sites, respectively. Received: 20 November 2009; Revised: 3 April 2010; Accepted: 20 April 2010